A case report of Brugada-like ST-segment elevation probably due to coronary vasospasm. Issue 9 (March 2018) - Yang, Lu; Ma, Guodong; Yu, Tianyu; Gao, Huikuan; Wang, Yongliang; Wu, Yongquan
Abstract: Rationale: Vasospastic angina is caused by sudden occlusive vasoconstriction of a segment of an epicardial artery, with transient ST-segment elevation on electrocardiography. Brugada Syndrome is an inherited arrhythmogenic cardiac disorder with a diagnostic electrocardiography characterized by coved-type ST-segment elevation in right precordial leads (V1-V3). Those two diseases usually have no correlation. In this report, we discuss an interesting case of a patient who was diagnosed as vasospastic angina according to his coronary angiography, but his electrocardiography showed a Brugada-like ST-segment elevation. Patient concerns: Our patient had a 9-month history of temporary but progressive substernal burning sensation with acid bilges of shoulders and arms, as well as profuse sweating at night. Diagnoses: Although he had no abnormal laboratory test result, no dysfunctional recorded echocardiogram or documented arrhythmia after being admitted to the hospital, his electrocardiography showed a Brugada-like ST-segment elevation. The coronary angiography result confirmed a diagnosis of vasospastic angina. Interventions: The patient was prescribed diltiazem, aspirin, isosorbide mononitrate and rosuvastatin and was strongly advised to quit cigarettes and alcohol. Outcomes: Follow-up at half a year turned out well. Lessons: This case links Brugada syndrome to coronary vasospasm. They may share similar mechanisms. Provocation test and gene test needs to be ran to distinguish both. Long-term follow-up is essential for it may bring a warning sign for life threatening ventricular arrhythmias.